Risk factors of acute kidney injury in patients with Stanford type B aortic dissection involving the renal artery who underwent thoracic endovascular aortic repair. Issue 1 (1st January 2021) - An, Xiuping; Guo, Xi; Ye, Nan; Bian, Weijing; Han, Xiaofeng; Wang, Guoqin; Cheng, Hong
Abstract: Background: Acute kidney injury (AKI) is one of the most common and serious complications in patients with type B aortic dissection (TBAD). This study aimed at investigating the incidence and risk factors of in-hospital AKI in TBAD patients involving the renal artery who underwent thoracic endovascular aortic repair (TEVAR) only. Methods: A total of 256 patients who were diagnosed as TBAD combined with renal artery involvement were included in this retrospective study. All patients were divided into the AKI group and the non-AKI group according to the KDIGO criteria. The risk factors for AKI were identified using a multivariate logistic regression model. Results: A total of 256 patients were included in this study, and the incidence of AKI was 18% (46/256). Patients in the AKI group were more likely to have a higher proportion of the youth, a higher level of body mass index, and a shorter time from onset to admission. Multivariate logistic regression analysis revealed that the youth (age ≤40 years) (OR: 2.853, 95%CI: 1.061–7.668, p  = .038) were prone to AKI, and lower estimated glomerular filtration rate (eGFR) (OR: 1.526, per 15-ml/min/1.73 m 2 decrease, 95%CI: 1.114–2.092; p  = .009), higher diastolic blood pressure (DBP) (OR: 1.418, per 10-mmHg increase; 95%CI: 1.070–1.879; p  = .015), and fasting blood glucose (FBG) ≥7 mmol/L on admission (OR: 2.592; 95%CI: 1.299–5.174; p  = .007) were independent risk factors for AKI. Conclusions: Higher incidence of AKI had been perceived in this study, most of them were young and middle-aged patients. Renopreventive measures should be considered in those high-risk patients with younger age, lower eGFR, higher DBP, and higher FBG on admission.